DETERMINATION OF BINDING ENTHALPY VALUE AT COMPLEX-FORMATION OF LIGAND WITH DNA (Proceedings of the YSU B: Chemical and Biological Sciences, 2016)
The value of binding enthalpy change (ΔH) due to DNA–ligand complexformation has been determined by Van’t–Hoff mode having dependence of binding constant (K) on the reverse value of absolute temperature. Calculations that were carried out for DNA–ethidium bromide and DNA–mitoxantrone complexes showed, that if ΔH is determined from the values of K at two different temperatures, the calculated value of ΔH in the error frame coincides with its experimental value.
Keywords: DNA, ethidium bromide, mitoxantrone, complex-formation, thermodynamic parameters